Endowments, fiscal federalism, and the cost of capital for states: Evidence from Brazil, 1891-1930 - André Martínez; Aldo Musacchio (Banco de México, 2009)
In this paper, we contribute to the discussion of what determines country risk by arguing that an important explanatory factor is the impact that commodities have on the capacity to pay. We use a newly created data base with state-level fiscal and risk premium data for Brazil states between 1891 and 1930 to show that Brazilian states with natural endowments that allowed them to export commodities that were in high demand ended up having higher revenues per capita and, thus, lower cost of capital. We also explain that the variation in revenues per capita across states was both a product of the variation in natural endowments and a commodity boom that had asymmetric effects among states. We end by running instrumental variable estimates using indices of export prices for each state to instrument for revenues per capita. Our IV estimates confirm our results that states with commodities that had higher price increases had lower risk premia.
Keywords: H71; H74; N26; N46; N96; 330; state public debt; fiscal decentralization; endowments; public revenue